Beliefs related to COVID-19 vaccine receipt in the Chicago area - Sarah Lomahan; Abigail Silva; Jessica Bishop-Royse; Paris Thomas; Molly A. Martin (Discover Public Health)
Abstract Background In Chicago, Illinois, USA, Black and Latinx populations experienced disproportionate rates of COVID-19 mortality compared to White populations. By February 2023, Black residents had the lowest levels of completing the primary vaccine series of any racial or ethnic group. The Chicagoland CEAL Program surveyed an urban minoritized population about COVID-19 beliefs and vaccination status. The purpose of this study was to evaluate this association and to determine if it could be explained by health care connectedness and discrimination. Methods Responses were collected from December 2021 to February 2023. Descriptive statistics were used to examine differences by vaccination status. Logistic regression was used to determine associations between each of the eight COVID-19 beliefs and not completing the primary vaccine series. Models were adjusted for sociodemographic factors, health care connectedness, and discrimination. Results From 760 surveys analyzed, 76% had completed the primary vaccine series. Most participants were women (74%), identified as nH Black (61%), and did not complete higher education (70%). Individuals who agreed that the vaccine was developed too quickly (aOR: 1.55 (0.99–2.43, p = 0.05)) and that the vaccine went against religious beliefs (aOR: 2.72 (1.67–4.43, p = < 0.0001)) had a greater likelihood of not completing the vaccine series. Conclusion Building and sustaining trustworthiness should be at the center of messaging surrounding vaccine uptake for Black and Latinx residents in an urban setting. Messaging should consider the importance of religion on vaccine uptake and collaborate with trusted messengers to address negative sentiment towards health behavior recommendations.